Ex vivo and in vivo evaluation of microemulsion based transdermal delivery of E. coli specific T4 bacteriophage: A rationale approach to treat bacterial infection - Rastogi V.; Yadav P.; Verma A.; Pandit J.K. (My University, 2025)
This study is focused on the development and evaluation of transdermal delivery of E. coli-specific T4 bacteriophages both ex-vivo and in-vivo using microemulsion as delivery carrier in eradicating the infection caused by E. coli. Microemulsions were prepared by mixing selected oil, surfactants and aqueous phase containing bacteriophages. The formulations were subjected to physicochemical characterization, ex-vivo and in-vivo permeation, stability studies, histological and immunofluorescence examination. The colloidal system exhibits a uniform size distribution, of finite size (150–320 nm). Transmission electron microscopy revealed the encapsulation of bacteriophage in the aqueous globule. Ex-vivo permeation across skin was successfully achieved as 6 × 106 PFU/mL and 6.7 × 106 PFU/mL of T4 permeated from ME 6% and 10%, respectively. ME 6% was found to be thermodynamically stable and in-vivo permeation resulted in 5.49 × 105 PFU/mL of bacteriophages in the blood of the E. coli challenged rats, while 2.48 × 105 PFU/mL was detected in germ free rats, at the end of the study. Infected rats that were treated with bacteriophage were survived while significant mortality was observed in others. Histological and IL-6 immunofluorescence examination of the tissues revealed the efficacy/safety of the therapy. The microemulsion-based transdermal delivery of bacteriophage could be a promising approach to treat the infections caused by antibiotic-resistant bacteria. © 2017 Elsevier B.V.